Integrated process scheme for the combined treatment of liquid wastes and municipal wastewaters: a process analysis. Issue 6 (1st February 2016) - Prisciandaro, Marina; Mazziotti di Celso, Giuseppe; Musmarra, Dino; Zammartino, Angelo
Abstract: In the following paper, we explored the possibility of integrating the treatment of civil sewage waters with that of liquid wastes, such as landfill leachate, by modifying a typical domestic wastewater process scheme of a real small wastewater treatment plant, located in Southern Italy. In the scheme of the analyzed process, which included the line of treatments for only domestic effluents, a specific line for the treatment of liquid wastes and leachate is added. Liquid wastes are thus pretreated and then simultaneously purified with the municipal wastewaters, in order to fulfill the limits for discharge into superficial water bodies. The process analysis, conducted by performing mass balances on the proposed scheme, has shown that in the case study examined, the treatments carried out (with the removal efficiencies assumed from the literature) are able to produce an effluent, whose concentrations are within the limits of the law dictated by the Italian Legislative Decree n. 152/06 for discharge in surface waters.